2008
DOI: 10.1248/cpb.56.129
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Absolute Configuration Determination of Aliphatic Sulfates as the Daphnia Kairomones Inducing Morphological Defense of a Phytoplankton-Part 2

Abstract: The countercations were not identified and expressed as M.Chart 1. Synthesis of (1S,2S)-2-ACyclo-COOH Ester 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Recently, the chemical nature of the natural colony-inducing chemicals released from Daphnia has been elucidated and the active substances were identified as different aliphatic sulfates (Yasumoto et al 2005; 2006; 2008a, b). These compounds are closely related to commonly used manmade anionic surfactants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the chemical nature of the natural colony-inducing chemicals released from Daphnia has been elucidated and the active substances were identified as different aliphatic sulfates (Yasumoto et al 2005; 2006; 2008a, b). These compounds are closely related to commonly used manmade anionic surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…The surfactant FFD-6 induced a response similar to the one evoked by the natural information conveying chemicals. These natural active substances have been extracted from Daphnia and could be identified as different aliphatic sulfates and sulfamates showing strong structural similarity with synthetic anionic surfactants (Yasumoto et al 2005, 2006, 2008a, b). Hence, despite various anionic surfactants have been classified as not dangerous to the environment with respect to their effect on Daphnia (Verge and Moreno 2000), the FFD-6-induced morphological effect might indicate potential adverse effects on the energy-flow from algae to higher trophic levels at concentrations previously thought to be safe.…”
Section: Introductionmentioning
confidence: 99%
“…Some types of kairomones have been isolated and identified. For example, aliphatic sulfates and sulfamates [242][243][244] as well as an artificial substitute (octyl sodium sulfate) have been found to induce colony formation in Scenedesmus sp. and Desmodesmus sp.…”
Section: Infochemicalsmentioning
confidence: 99%
“…A first attempt to analyse the infochemicals released by daphnids was made by Van Holthoon et al (2003). Some years ago, Yasumoto et al (2005Yasumoto et al ( , 2008 reported a major breakthrough with a bioassayguided characterization of infochemicals from a 10-kg sample of Daphnia. After several chromatographic steps, eight aliphatic sulphates that are active at low concentrations (\1 ng ml -1 ) were isolated and fully characterized.…”
Section: Morphological Defences In Phytoplanktonmentioning
confidence: 99%